2022
DOI: 10.1007/s13278-022-00925-5
|View full text |Cite
|
Sign up to set email alerts
|

Favorite YouTubers as a source of health information during quarantine: viewers trust their favorite YouTubers with health information

Abstract: During quarantine, between March and May 2020, YouTubers disseminated information about Covid-19 and the quarantine. The objectives of this study are (1) to explore whether YouTubers are considered as reliable sources of information regarding quarantine by French social media users, (2) to evaluate the link between the parasocial relationship with a favorite YouTuber and the level of trust in the information provided by this YouTuber and (3) to test the effectiveness of the favorite YouTuber as a source of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have inconsistently reported that the quality of videos providing health-related information is lower for videos uploaded by individuals and higher for videos from educational institutions or medical professionals. 7,13 This is because the YouTuber videos obtained in this study included information from the ROBOCARE CENTER, which provides the HAL exercise program and staff information. The ROBOCARE CENTER has trainers and physical therapists with specialized knowledge and experience in HAL.…”
Section: Characteristics Of Youtuber Videosmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have inconsistently reported that the quality of videos providing health-related information is lower for videos uploaded by individuals and higher for videos from educational institutions or medical professionals. 7,13 This is because the YouTuber videos obtained in this study included information from the ROBOCARE CENTER, which provides the HAL exercise program and staff information. The ROBOCARE CENTER has trainers and physical therapists with specialized knowledge and experience in HAL.…”
Section: Characteristics Of Youtuber Videosmentioning
confidence: 99%
“…YouTube is the most commonly used video social network and is recognized as an important online information source. 6,7 Videos on rehabilitation and healthcare are also uploaded and used as a tool for sharing patient experiences and providing education. 6,8 YouTube enables anyone to post videos for free, and influencers who regularly upload videos to their personal YouTube channels are known as YouTubers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborating with influencers who already have an established audience in the target community can enable health messaging to be tailored and disseminated in a way that feels more personally relevant to members of those communities, and takes advantage of the conversational dynamics and social influence embedded in online networks [ 16 ]. Although influencers rarely have health-related expertise, some research suggests that they may still be perceived as trusted sources of health information among their followers [ 17 ]. Working with influencers could also present health practitioners with an opportunity to bypass filter bubbles and self-curation in order to reach populations that may not have an active interest in health information [ 16 ].…”
Section: Approaches To Make Health Communication Efforts More Precise...mentioning
confidence: 99%